Analysis of Telomere Lengths in p53 Signatures and Incidental Serous Tubal Intraepithelial Carcinomas Without Concurrent Ovarian Cancer. (August 2019) - Asaka, Shiho; Davis, Christine; Lin, Shiou-Fu; Wang, Tian-Li; Heaphy, Christopher M.; Shih, Ie-Ming
Abstract : Telomere alterations represent one of the major molecular changes in the development of human cancer. We have previously reported that telomere lengths in most serous tubal intraepithelial carcinomas (STIC) are shorter than they are in ovarian high-grade serous carcinomas (HGSC) or in normal-appearing fallopian tube epithelium from the same patients. However, it remains critical to determine if similar telomere alterations occur in TP53 -mutated but histologically unremarkable "p53 signature" lesions, as well as incidental STICs without concurrent HGSC. In this study, we quantitatively measured telomere lengths by performing telomere-specific fluorescence in situ hybridization in conjunction with p53 immunolabeling in 15 p53 signatures and 30 incidental STICs without concurrent HGSC. We compared these new results with our previous data in paired STICs and concurrent HGSCs. We found that most p53 signatures (80%) and incidental STICs without HGSC (77%) exhibited significant telomere shortening compared with adjacent normal-appearing fallopian tube epithelium ( P <0.01). Interestingly, however, p53 signatures and incidental STICs without HGSC displayed longer telomeres and less cell-to-cell telomere length heterogeneity than STICs associated with HGSC ( P <0.001). These findings indicate that telomere shortening occurs in p53 signatures, the earliest precancer lesion. Moreover, incidental STICs without concurrent HGSC are indeed similar to p53 signatures as they have less telomere shortening and less cell-to-cell telomere length heterogeneity than STICs associated with HGSC. Abstract : Supplemental Digital Content is available in the text.